New Records of the Spider Fauna from Sarawak, Malaysia - Nasir, Dzulhelmi Muhammad; Xing, Wong Chun; Mamat, Nur Syahirah; Pui, Yong Min; Sulaiman, Badiozaman (JURNAL BIOLOGI INDONESIA, 2016)
SHORT COMMUNICATIONÂ New Records of the Spider Fauna from Sarawak, Malaysia